Some Observations on Natural Law (Diametros, 2013)
The paper offers some observations with a view to correcting ostensible misunderstandings of the so-called New Natural Law (“NNL”) theory, concluding that the NNL theory is unworkable and unsustainable, even on its own terms. It is argued that the NNL theory is based on fundamental misunderstandings of the nature of necessity in Aquinas; the nature of propositions which are “known in themselves” (per se nota); and the nature of fundamental practical reasoning. It is argued that, where the NNL theory differs from that of Aquinas, the latter provides a better framework for the development of accounts of natural law today.
Keywords: natural law; Aquinas; is-ought distinction